Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Pada Sate Kambing Muda “Mba Ita” di Sukoharjo - Annasya Al Sadhilla; Berta Berlianda; Rayhan Gunaningrat; R.Taufiq Nur Muftiyanto (Pusat Riset dan Inovasi Nasional, 2025)
The increasingly rapid economic development has given rise to intense competition in the business world, a type of culinary business that offers food products that use goat meat as the main ingredient. This research was carried out with the aim of finding out how much influence product quality and price have on purchasing decisions. Researchers use quantitative research, survey research methods, descriptive analysis. The results of testing the validity of variable data using SPSS are as follows. The Sig0 value of the KMO and Bartlet's numbers is 224,576 with a significance value of 0.000. N100 based on the output it is known that the significance value of Asymp. Product quality and price simultaneously influence purchasing decisions for Sate Kambing Muda Mba Ita in Sukoharjo.